2006
DOI: 10.2166/wst.2006.235
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline and acid hydrolytic processes in aerobic and anaerobic sludges: effect on total EPS and fractions

Abstract: Sludge samples from an upflow anaerobic sludge blanket (UASB) reactor and four submerged aerated biofilters (BFs) of a wastewater treatment plant (1,000 inhab.) were processed at bench scale by alkaline and acid hydrolysis with the objective to evaluate the organic matter solubilization, volatile solids (VS) destruction and the effect of hydrolytic processes on the extracellular polymeric substances (EPS) fraction of the sludge samples. The results showed that alkaline hydrolysis of sludge samples treatment wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…According to the literature data alkali pretreatment is more effective that acid treatment [32]. Cassini et al [33] proved that the same doses of H2SO4 and NaOH (20 mmol/L) allowed for solubilisation COD in the sludge at level 11% and 60%, respectively. Banu et al [34] showed that optimal dose of NaOH for sludge pretreatment is 1600 mg/L (time of reaction 3 hours).…”
Section: Chemical Pretreatmentmentioning
confidence: 99%
“…According to the literature data alkali pretreatment is more effective that acid treatment [32]. Cassini et al [33] proved that the same doses of H2SO4 and NaOH (20 mmol/L) allowed for solubilisation COD in the sludge at level 11% and 60%, respectively. Banu et al [34] showed that optimal dose of NaOH for sludge pretreatment is 1600 mg/L (time of reaction 3 hours).…”
Section: Chemical Pretreatmentmentioning
confidence: 99%
“…Firstly, because the generated compounds are the substrates, which are converted by another group of microorganisms (e.g., syntrophic bacteria) in acetogenesis. Secondly, it was reported that weak acids such as propionic acid, can loosen the structure of lignocellulose, resulting in an improved overall hydrolysis rate, owing to the increased accessibility of the substrate for the enzymes (Cassini et al, 2006). The fact that a correlation was observed between the high hydrolytic activity and high biogas yield during anaerobic digestion suggests that the pretreatment of cellulose/lignocellulose substrates is crucial for promoting biogas productivity and biogas technology development (Haruta et al, 2002;Wongwilaiwalin et al, 2010;Guo et al, 2011).…”
Section: Simulation Of the Anaerobic Digestion Processmentioning
confidence: 99%
“…Therefore, it is possible to use thermal pretreatment for MBM disposal without supplying extra heat input. As proteins are the main component of MBM, alkaline pretreatment would be more efficient than acid pretreatment for the solubilization of MBM, which has been demonstrated in the hydrolysis of protein-dominating activated sludge [11,12]. However, the effectiveness of alkaline pretreatment of MBM has not been determined.…”
Section: Kg Inmentioning
confidence: 99%